Effects of the Combinations of Rhizobacteria, Mycorrhizae, and Seaweed, and Supplementary Irrigation on Growth and Yield in Wheat Cultivars - Vafa, Z Najafi; Sohrabi, Y; Sayyed, R Z; Luh Suriani, Ni; Datta, Rahul (Plants (Basel, Switzerland), 2021)
Wheat is a staple food consumed by the majority of people in the world and its production needs to be doubled to feed the growing population. On the other hand, global wheat productivity is greatly affected due to drought and low fertility of soil under arid and semi-arid regions. Application of supplementary irrigation and plant growth-promoting rhizobacteria (PGPR) has been suggested as sustainable measures to combat drought stress and to improve soil fertility and, hence, crop yield. This research was undertaken to study the effect of supplementary irrigation together with a combination of various PGPR on the growth and yield of two wheat cultivars, namely Sardari and Sirvan. The results of variance analysis (mean of squares) showed that the effect of irrigation, cultivar, and irrigation and biofertilizer and irrigation on height, spike length, seed/spike, and numbers of spikes/m2, 1000-seed weight, and grain yield were significant at 1% probability level. The effect of cultivar and irrigation interactions showed that the highest grain yield was obtained in a treatment with two additional irrigations in Sirvan cultivar (5015.0 kg/ha) and Sardari (4838.9 kg/ha) as compared to the 3598 kg/ha and 3598.3 kg/h grain yield in Sirvan and Sardari cultivars with similar treatment, but without irrigation, i.e., dryland farming. Drought conditions significantly affected the wheat grain yield while supplementary irrigation resulted in 39.38% and 34.48% higher yields in Sirvan and Sardari cultivars.
Keywords: drought stress; wheat; biofertilizers; irrigation; mycorrhiza